THE WORD FORMATION OF NOUNS IN ENGLISH LANGUAGE - Eshmuratova Sholpan; Naimova Nazira Kairatdinovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. This article explores the intricate processes involved in the formation of nouns in the English language. It delves into various mechanisms such as derivation, compounding, conversion, clipping, blending, borrowing, acronyms, initialisms, and back-formation. By examining these methods, the article sheds light on how English continually evolves to accommodate new concepts and cultural influences.